Depression Among Undergraduate Medical Students - Basnet, Bibhusan; Jaiswal, M; Adhikari, B; Shyangwa, PM (Kathmandu University Medical Journal, 2013)
Background Psychological stress is common in medical school and associated with depression. Medical education is grooming in Nepal, but only few studies are done concerning mental health of medical students. Objective To assess the prevalence of depression among medical students at different levels of education and find about their stressors. Methods A cross sectional, questionnaire-based survey was carried out among the undergraduate medical students of B.P.Koirala Institute of Health Sciences, Nepal. 50 students each from Bachelor of Medicine and Bachelor of Surgery (MBBS) first and third year were enrolled in the study conducted between November 2008 to January2009. The depression levels were assessed using Zung depression scale. Students were asked to complete the questionnaire and then the depression levels calculated .The stress inducing factors during their course of medical education were also assessed. Results The overall prevalence of depression among the students was 29.78 percent. The prevalence of depression in first and third year was 36.74and 22.22 percent respectively. The prevalence of depression was 32.43 percent among female students versus 28.07 percent in male students. Both first and third year students gave high ratings to academic stress and hectic lifestyle as the main stress inducing factors. Conclusion The prevalence of depression is seen especially in the first year medical students. So, attempts should be made to alleviate the stressors right from the time they join medical school. Since academic stress proved to be one of the major factors, measures to make the academic curriculum more student-friendly are suggested. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 56-59 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8021